Enfermedades más comunes de la raicilla (Cephaelis ipecacuanha Rich) en Costa Rica y recomendaciones para su cultivo (ING) - Rivera C., German (1991)
Ipecacuanha (Cephaelis ipecacuanha Rich) sanitary studies in the North region of Costa Rica, showed the presence of some economically important diseases in this crop. The most frequent diseases were: antracnose (Colletotrichum sp.), leaf spot (Mycena citricolor Sacc.), Stem blight (Sclerotium rolfsii Sacc.) and wilt (Fusarium sp.) Less frecuent diseases were leaf spots caused by: Capnodium sp, Leptothyrium sp, Pestatolia sp, Exosporium sp, Periconiella sp, Rhyzoctonia sp and Cephaleurus virescens Kunze. Verticillium sp was found as a vascular system pathogen.As a result of some field trials and from the farmer´s experience, some general plant disease control practices are recomended  on aspects such as: seed sanitation and desinfection, soil management, plant spacing, weed management, shade regulation, genetic resistance and chemical control.